1987
DOI: 10.1177/000456328702400104
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Abnormalities in Anorexia Nervosa and Bulimia

Abstract: SUMMARY.We report the biochemical results in 90 women presenting to an eating disorders clinic: 61 who had bulimia, 22 with anorexia nervosa and seven unclassified. The results were compared with 30 control women. The group of women with an eating disorder had significantly higher concentrations of total CO 2 , calcium, AST, ALT. ALP, albumin and cholesterol and significantly lower concentrations of potassium, chloride and phosphate in the plasma. The elevated calcium could be accounted for in part by an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
2
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 19 publications
3
40
2
2
Order By: Relevance
“…Cravario et al (5) reported that only one of27 patients with an average BMIof 14.4 ± 2.0 (mean ± SD) showed elevated serum aminotransferase levels. Mira et al (6) reported that 2 of 22 anorectic patients, with body weight 73.2 ± 9.6% of standard body weight, showed elevated serum aminotransferase levels. In the report of Fichter and Pirke (7), there was no difference in ALTand ASTbetween groups of patients with less than 60%, 61-90%, and 91-1 10% of ideal body weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cravario et al (5) reported that only one of27 patients with an average BMIof 14.4 ± 2.0 (mean ± SD) showed elevated serum aminotransferase levels. Mira et al (6) reported that 2 of 22 anorectic patients, with body weight 73.2 ± 9.6% of standard body weight, showed elevated serum aminotransferase levels. In the report of Fichter and Pirke (7), there was no difference in ALTand ASTbetween groups of patients with less than 60%, 61-90%, and 91-1 10% of ideal body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we started a prospective study to clarify the clinical implication of serum aminotransferase elevation in anorexia nervosa. To date, numerous studies have discussed the elevation of serum aminotransferase levels in the patients with anorexia nervosa (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). However, there have been no consistent patterns in the results and the clinical implication has not been clarified (2).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, certain eating disorders can cause transaminitis, including anorexia, bulimia and eating disorder not otherwise specified [29][30][31]. However, a large study of patients with eating disorders determined that hepatic dysfunction was not common among eating disorders and liver damage could often be attributed to low weight [32].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, contrary to popular belief, hypoalbuminemia is rarely present in cases of isolated calorie malnutrition. 12 Rather, hypoalbuminemia is a marker of the systemic inflammatory response and is associated with increase morbidity and mortality among hospitalized patients. 13 Therefore, serum albumin concentration can be used as a nutrition screening tool at the time of ICU admission.…”
Section: Determination Of Nutrition Requirements Nutrition Assessmentmentioning
confidence: 99%